Discourses in colombian and swedish syllabuses - Lucely Figueroa Suárez; Ulrika Ryan (Prometeica, 2023)
Recently there has been a trend to include Computer Programming and Environmental Education in national syllabuses due to the accelerated technological development and the climate crisis. This study aims to investigate how notions of Action Competence, Computer Programming and Environmental Education converge or not in Discourses in educational policy documents in Colombia and Sweden. Action Competence is the capacity to play an active role and act intentionally in addressing issues that matter to students. The Discourses that we identified are: (1) Qualification is what counts, (2) Programming has little to do with environmental education, and (3) Students are not decision makers.